Racial and Treatment Center Differences on Time to Treatment Initiation for Nonsmall Cell Lung Cancer Patients Receiving Radiation Therapy As an Initial Treatment (Mary Ann Liebert, 2022)
Objective: Because time to treatment has been shown to be associated with increase in the risk of death for Non Small Cell Lung Cancer (NSCLC) patients, we examined the prevalence and magnitude of racial disparities in mean time to radiation therapy (TTRT) for Stage I-III non-small cell lung cancer patients across a variety of treatment facilities. Methods: Utilizing the United States National Cancer Database (NCDB), we determined differences in TTRT between different races and different treatment facilities. Results: Concordant with past research, we found that non-White patients and patients treated at academic facilities, regardless of race, have longer mean TTRT, and that racial disparities in TTRT extend across all treatment facilities (all p<0.05). Conclusions: These findings shed light on the potential presence of and impact of structural racism on patients seeking cancer treatment, and the need for further investigation behind the reasonings behind longer TTI for non-White patients. To elucidate the real-world applicability of these results, further investigation into the societal determinants that perpetuate disparity in time to radiation therapy, and potential interventions in the clinical setting to improve cultural and racial sensitivity among healthcare professionals is recommended.